SEPARATING SOCIAL WELFARE SERVICES AND SOCIAL WELFARE GRANTS: CHALLENGES AND OPPORTUNITIES - September, Rose (Social Work/Maatskaplike Werk, 2007)
As a consequence of the fundamental reconstruction and development processes, including a large-scale macroeconomic stabilisation strategy, South Africa’s economic growth has consistently averaged 3% over the last decade. It is expected that the government’s new Accelerated and Shared Growth Initiative for South Africa (AsgiSA) will increase the economic growth rate from its current level to 4.5% by 2010 and 6% by 2014 (Yemek, 2006). Yet with the majority of its citizens living in poverty (with less than 1 per day), South Africa remains one of the most unequal societies in the world (Statistics South Africa, 2004). Although there has been some improvement over the last decade, the stubborn legacy of apartheid persists and can be seen in the concentration of poverty and underdevelopment in black communities. Twenty four million of South Africa’s population of 45 million are black females who live below the poverty datum line (Statistics South Africa, 2004). Using the expanded definition of unemployment, Statistics South Africa (2004) estimated that 41% of the economically active population was unemployed in 2004. There is, therefore, growing concern that the strategies employed thus far to raise the unacceptably low standards of living of South Africa’s vulnerable populations, who continue to lack access to basic services and employment opportunities, are lagging far behind what is needed.